Development of Agent-based Models for Economic Simulation - Šalamon, Tomáš; Řepa, Václav, 1958-; Hřebejk, Petr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2010)
This thesis is about the development of agent-based models that are a method of simulation of economic processes and environments using multi-agent systems. Agent-based modeling seems to be an unappreciated approach that is expected and has a potential for a much wider application than it actually has. The purpose of thiswork is to evaluate the reasons for such situation and to offer solutions. The following were identified among the reasons for a low utilization of the method: a wide gap between theory and practice in the field, doubtful reliability of the method, lowconfidence in its results, complexity, missing methodologies, problems with suitable development frameworks, limitations of computational performance, a lack of awareness among the public and certain other problems. Agentology; (i.e. a methodology for the development of agent-based models) was proposed in this thesis in order to address issues regarding the development of agent-based models. There are six defined roles of project participants in the methodology: expert, analyst, modeler, platform specialist, programmer and tester. The design and development process consists of four phases and nine steps beginning with task formulation, conceptual modeling, and platformspecific modeling to the development of the system. For the design phases, agent modeling language for agent-based models was derived.
Vedoucí práce: Václav Řepa
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2010
Rok obhajoby 2010
Keywords: informatika [obor disert. práce]; disertace; dissertations